Tinjauan Hukum terhadap Penggunaan Game oleh Anak sebagai Konsumen Digital di Indonesia - Veronica Piqe Febeline; Valerie Celine (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of digital technology has transformed children’s patterns of interaction through online games, which serve both as entertainment and transactional spaces. As digital consumers, children are entitled to protection equal to adults, yet they remain vulnerable to risks such as inappropriate content, fraud, data manipulation, and exploitation. Despite the existence of legal frameworks like the Consumer Protection Law, the Child Protection Law, and the Electronic Information and Transactions Law, this study reveals that these laws do not specifically address children as a vulnerable group in the digital environment. This research employs an empirical normative approach to highlight the shortcomings of current regulations. Given the rapidly growing use of digital platforms by children, stronger regulatory measures, greater parental involvement, and increased responsibility from platform providers are essential to ensure the fulfillment of children’s rights and provide adequate protection in the digital space. These findings emphasize the need for comprehensive legal reform to safeguard children’s digital rights.